Pengembangan Bahan Ajar LKPD (Lembar Kerja Peserta Didik) Biologi Sains Berbasis Pendekatan Inquiry Terbimbing Pada Sub Pokok Bahasan Fotosintesis - Nursafiah Nursafiah (Keguruan, 2020)
Based on an observation done at Senior High School 1 Badar, the most common problems found was on student worksheets (LKPD) used in the learning process which only in the form of question sheets so that they only focused on verbalism skills. Based on this issue, the researcher want to develop the students worksheet (LKPD) and find out the appropriateness of the development in student worksheet based on guided inquiry. This is researh and development (R D), which is a method used to produce a particular product by testing the effectiveness of the product. Validation of material experts on the content feasibility component shows the total score of 194 with a percentage of 88 .18%, with the "Very Eligible" category. Validation of material experts on the linguistic component shows the results of the total score of 115 with a percentage of 82.14%, with the "Very Eligible" category. Validation of material above on the presentation component shows the total score of 124 with a percentage 88.57% in the Very Eligible category. Based on the above calculations, the observations made byÂ  the experts about the entire part of the teaching materials for student worksheets reached 86.29%. If it is matched with the table of eligibility criteria, then this achievement score is included in the Very Eligible criteria. Thus, it can be concluded that the student worksheet (LKPD) Based on the guided inquiry approach can be used in the learning process in secondary schools.